Isolation and identification of burkholderia species from water samples - Nasir, Mirna (Universiti Malaysia Sarawak (UNIMAS), 2015)
Water has a strong association with soil, the high microbial presence in soil directly affects the microbial presence in water within the same vicinity. Water is an important element in our daily lives and hence the presence of any microbes in the water may potentially cause severe infections in humans and animals. Burkholderia pseudomallei currently denoted as Tier I Select Agent and it can caused disease known as melioidosis. The aim of this project is to isolate and identify Burkholderia species from the water samples, which water sources are much related to human activities. There were 8 total sites included in this project and originally water samples were collected from Tawau, Sabah and Kota Samarahan, Sarawak. Moore's swabs were used for the water samples collection, and their sources were mainly from lake, pond, construction sites and orchard. The swabs were used because it is more cost effective compared to conventional method. All water samples collected were cultured on Ashdown's agar. Fifty-six percent of the water samples collected around Tawau and Kota Samarahan, were culture positive for Burkholderia spp. and less than 2% of them were culture positive for B. pseudomallei.